Contribution of COVID Antigenic RDT to the Management Strategy of COVID-19 Pandemic in a Senegalese Company. Issue 4 (25th April 2022) - Sagna, Asséga Sylvain; Seydi, Aïssatou Goundo; Gueye, Modou Mbacké; Fall, Mame Thioro Aïssatou; Mansuy, Jean Michel
Abstract : Our article suggests that Occupational health care services in developing countries should resort and popularize COVID-19 rapid diagnostic tests to contribute to the fight against the pandemic and all its consequences on the production potential of companies, especially. Abstract : Objective: To describe the contribution of the rapid antigen diagnostic testing (RDT) to the management strategy of the COVID-19 pandemic. Methodologies: The protein chain reaction (PCR) and the RDT have been performed on each COVID-19 suspected workers from December 2020 to September 2021. Results: A total of 286 people tested. A positivity rate of 38.1% was recorded. The average time to obtain PCR results was 8.3 days. 54.8% ( n = 142) of the RDT were followed by a PCR for confirmation or invalidation and 100% of positive cases with Ag-RDT were confirmed by the PCR. We have noticed a 58.3% reduction of lost work days due to COVID-19, since the use of the Ag-RDT. Conclusion: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) rapid diagnostic tests are efficient. They have enabled early treatment of COVID-19 patients, helped hold back the spread of the disease in a high-risk professional environment, and reduced the impact of the pandemic on a vital sector in developing countries.